2019
DOI: 10.1088/1742-6596/1391/1/012157
|View full text |Cite
|
Sign up to set email alerts
|

Virtual laboratories of electromagnetism for education in engineering: A perception

Abstract: The influence of virtual tools as didactic means towards the study of electromagnetism phenomena takes greater relevance every day at the Universidad del Magdalena due to the inclusion of a visual and dynamic element beyond the reading of physical text books and even the development of laboratories real electromagnetism. This article shows a very positive perception on the part of the engineering students regarding the advanced virtual laboratories of electromagnetism, influencing the learning of physical conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…Based on the recapitulation, description and data analysis, it was found that there was a significant effect between teacher professional certification (X) on work motivation (Y 1 ). Related to this matter, this acquisition was in accordance with the results of several previous studies conducted by [17] which are in line with these results and stated that the teacher certification program has a significant effect on motivation.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the recapitulation, description and data analysis, it was found that there was a significant effect between teacher professional certification (X) on work motivation (Y 1 ). Related to this matter, this acquisition was in accordance with the results of several previous studies conducted by [17] which are in line with these results and stated that the teacher certification program has a significant effect on motivation.…”
Section: Discussionsupporting
confidence: 92%
“…This is because the Digital Electronics material is of high complexity and contains quite a lot of mathematical concepts, so a fairly high mathematical ability is needed, thus students who have high mathematical abilities will more easily and quickly understand Digital Electronics material and apply it to problems physics compared to students who have the low mathematical ability. This is in line with research conducted (González et al 2019) that in physics, mathematics plays a major role. In addition to its ability to solve physics problems from simple to more complex, mathematics is very helpful in one's reasoning in exploring the intricacies of physics which require a quite high reasoning.…”
Section: The Influence Of Cognitive Affective and Psychomotor Learning Achievement Of Students Who Have High And Low Mathematical Abilitisupporting
confidence: 92%
“…The Arduino Uno microcontroller gives students the freedom to design a wide variety of projects, from simple to complex. This design process encourages creative thinking skills in creating innovative solutions to given problems or tasks (González et al, 2019); Decision Making. In developing a project with the Arduino Uno, students need to make various decisions, such as component choices, design approaches, and programming strategies.…”
Section: Discussionmentioning
confidence: 99%